THE ART OF PUNCTUATION: ENHANCING LANGUAGE THROUGH MARKS - Abdurakhmonova, Asila Asliddin qizi (Educational Research in Universal Sciences, 2023)
Punctuation is a crucial aspect of written language that helps to clarify meaning and enhance comprehension. Without proper punctuation, written text can be difficult to understand and ambiguous. Different languages and writing systems have their own set of punctuation standards, and in this article, we will explore the punctuation standards in English and their grammar-logic features.